Deep brain stimulation of the anterior nuclei of the thalamus relieves basal ganglia dysfunction in monkeys with temporal lobe epilepsy. (21st October 2020) - Du, Tingting; Chen, Yingchuan; Shi, Lin; Liu, Defeng; Liu, Yuye; Yuan, Tianshuo; Zhang, Xin; Zhu, Guanyu; Zhang, Jianguo
Abstract: Aims: Deep brain stimulation of the anterior nuclei of the thalamus (ANT‐DBS) is effective in temporal lobe epilepsy (TLE). Previous studies have shown that the basal ganglia are involved in seizure propagation in TLE, but the effects of ANT‐DBS on the basal ganglia have not been clarified. Methods: ANT‐DBS was applied to monkeys with kainic acid–induced TLE using a robot‐assisted system. Behavior was monitored continuously. Immunofluorescence analysis and Western blotting were used to estimate protein expression levels in the basal ganglia and the effects of ANT stimulation. Results: The seizure frequency decreased after ANT‐DBS. D1 and D2 receptor levels in the putamen and caudate were significantly higher in the ANT‐DBS group than in the epilepsy (EP) model. Neuronal loss and apoptosis were less severe in the ANT‐DBS group. Glutamate receptor 1 (GluR1) in the nucleus accumbens (NAc) shell and globus pallidus internus (GPi) increased in the EP group but decreased after ANT‐DBS. γ‐Aminobutyric acid receptor A (GABAA ‐R) decreased and glutamate decarboxylase 67 (GAD67) increased in the GPi of the EP group, whereas the reverse tendencies were observed after ANT‐DBS. Conclusion: ANT‐DBS exerts neuroprotective effects on the caudate and putamen, enhances D1 and D2 receptor expression, and downregulates GPi overactivation, which enhanced the antiepileptic function of the basal ganglia. Abstract : ANT‐DBS exerts neuroprotective effects on the caudate and putamen, enhances D1 and D2 receptor expression, and downregulates GPi overactivation, which enhanced the antiepileptic effect of the basal ganglia.